25 Ways to Win With People : How to Make Others Feel Like a Million Bucks - Maxwell, John C., 1947- (Nashville Thomas Nelson, 2005)
You've read John Maxwell's best-selling Winning with People, and now you're ready for some specific action steps to build on the knowledge you gained. 25 Ways to Win With People has just what you need! This complementary companion to the full-sized book is ideal for a quick refresher course on interpersonal relationships
Include Notes
Keywords: Interpersonal communication -- Interpersonal communication--Religious aspects--Christianity